Radionuclide concentration and radon exhalation in new mix design of bricks produced reusing NORM by-products: The influence of mineralogy and texture. (10th November 2020) - Coletti, Chiara; Brattich, Erika; Cinelli, Giorgia; Cultrone, Giuseppe; Maritan, Lara; Mazzoli, Claudio; Mostacci, Domiziano; Tositti, Laura; Sassi, Raffaele
Highlights: Determination of radioprotection safety requirements for bricks reusing by-products. An integrated approach based on radioactivity measurements, mineralogy and texture. Texture evolution during firing determine changes radon mobility and exhalation. Abstract: Many industrial by-products contain Naturally Occurring Radioactive Materials (NORM) that normally represent a cost in terms of monitoring, risk management and storage. When included in new mix designs of bricks, these materials may become a valuable sustainable resource. Before marketing, companies involved in development and commercialization of these new building materials ensure safety related to radiation, usually by assessing radon-related risk. According to the Council Directive 2013/59/Euratom, both raw materials and final products used in building constructions need to be tested for activity concentration. The present work explores the radionuclide concentration and the radon exhalation of bricks obtained recycling different types of potentially radioactive wastes: i) trachyte as by-product resulting from quarrying operations, and ii) two different types of industrial sludge derived from ceramic tiles industry. Raw materials were studied to foresee any potential radioactive risk derived from their use as secondary raw materials, while bricks were investigated to assess the influence of mineralogy and texture on their radioactive properties and their effective radon-risk. The results obtained here show that, although radon emanation in bricks is primarily determined by radionuclide concentration in the raw materials, textural features significantly affect radon mobility and exhalation.